FERMENTASI SUSU KERBAU (DADIAH) DARI PERSPEKTIF ETNO-ILMIAH, KEARIFAN LOKAL MINANGKABAU, SUMATERA B - amelia dwi putri; Aulia Azhar (Al-Alam: Islamic Science Education Journal, 2026)
Dadiah is a traditional fermented milk product from Minangkabau made from fresh buffalo milk. The milk is placed in a bamboo container, covered with banana leaves, and fermented for 1-2 days at room temperature. The tradition of making dadiah has been passed down from generation to generation and is still practiced today using traditional methods. This research aims to examine local Minangkabau wisdom regarding fermented buffalo milk (dadiah) from an ethnoscience perspective, including history, the manufacturing process, as well as the role and function of dadiah in ethno pharmaceutical, ethnomedical, ethno physical and ethnobiological aspects. The research carried out was qualitative research using literature study and observation methods. Dadiah not only acts as a traditional preparation, but in it there is an Ethnoscience ecology such as Ethnophysics, Ethnobiology, Ethnochemistry, Ethnopharmacy and Ethnomedicine which we can study to understand more deeply the relationship between local traditions, health and science. Making dadiah involves the role of lactic acid bacteria in the fermentation process that occurs in bamboo containers.